Transferts. - Tata Cissé, Youssouf; Fabian, Johannes; Wendl, Tobias; Paleis voor Schone Kunsten, Brussel; Judong, Anne; Muteba Luntumbue, Toma (Bruxelles : Africalia vzw, 2003., 2003)
Bachiri, Brahim ; Benohoud, Hicham ; Bidjocka, Bili ; Bouabré, Frédéric Bruly ; Carlos, Isaac ; Damag, Gaston ; D.O.F. ; Donkor, Godfried ; Anatsui, El ; Jaar, Alfredo ; et al.
In Paleis voor Schone Kunsten, Brussel, 21 juni t.e.m. 14 september 2003
Toma Muteba Luntumbue
kunstcatalogus
Keywords: Afrika